Towards a compact macroform: commuter line optimization in Istanbul. Issue 3 (4th May 2019) - Eryılmaz, Yaşasın; Tezcan, Hüseyin Onur
Abstract: In many cities, different developments in economic, social, and physical environment significantly influence the transportation demand. When the demand could not be matched by capacity expansions, sustainability is tried to be attained via various demand management strategies. In this study, optimization of the commuting trips for demand management is evaluated. The main aim of this study is to offer a transport incentive program that redistributes the benefits gained from the modification of trip distances. This program proposes to transfer a certain amount of money to the individuals affected from a policy change and instigates the relocation of some individuals. Although the program's overall aim is to canalize as much users as possible to relocate, the money is due to be transferred without any restrictions or constraints and looks for the equilibrium of the costs and the benefits by comparing the current state and the situation after the policy change.